Perbandingan Hukum Islam dan Hukum Positif Terhadap Hak Kebebasan Beragama - Fajar Nur Alamsyah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
This article explains about Religious Freedom in Article 28E of the 1945 Constitution by using the author's analysis using the glasses of Islamic Law and Positive Law. Human freedom in their social life aims to strengthen their social relations to obtain their necessities of life. However, there are often conflicts in fulfilling the interests of each individual, resulting in a loss of warmth among citizens. In Islam human freedom is one of the various noble values which is also the main goal of the maqasid syari'ah. Islam itself knows about Riddah law. In Islam Riddah is a conversion of religion from Islam to another religion and is a category of kufr which in classical jurisprudence is punishable by death. In Indonesian law itself as a respect and guarantee for the survival of every individual, the government then ratifies the universal declaration of human rights, civil and political rights and economic, social and cultural rights into the Indonesian legal system. In particular, the right to freedom of religion is regulated in the 1945 Constitution Article 28E, however threats still come and go to haunt Indonesian people who have exercised their freedom to choose and embrace their religion. So it is important to reconstruct how the guarantee of the right to freedom of religion in the Indonesian constitution and analyze it in the perspective of Islamic law and positive law.Keywords: Religious Freedom, Islamic Law, Positive Law